105k views
1 vote
For f(x) = x + 3 and g(x) = 2x + 1 , find the following functions. c and d

For f(x) = x + 3 and g(x) = 2x + 1 , find the following functions. c and d-example-1

1 Answer

5 votes

c)

We know that:


(f\circ g)(x)=2x+4

to find the function at x=1 we just plug this value of x in the expression found:


(f\circ g)(1)=2(1)+4=2+4=6

Therefore:


(f\circ g)(1)=6

d)

We know that:


(g\circ f)(x)=2x+7

Then we have:


(g\circ f)(1)=2(1)+7=2+7=9

Therefore:


(g\circ f)(1)=9

User David Faber
by
6.6k points